PENINGKATAN KOMPETENSI SISWA SEKOLAH MENENGAH KEJURUAN MELALUI PENERAPAN PEMBELAJARAN KETERAMPILAN WIRAUSAHA BIDANG BOGA SEBAGAI BEKAL KECAKAPAN HIDUP (LIFE SKILL) - Marwanti, Marwanti; Yuriani, Yuriani; Ekawatiningsih, Prihastuti (Universitas Negeri Yogyakarta, 2009)
This civil serving program was aimed to give live skills basedentrepreneurship as an alrernative asset for vocational school students,especially for vocational school number I at Depok Sleman. The students,majoring in food and beverage, was expected to have knowledge and live skills which was needed to enter the work World, whether it was a privateBusiness or working in product or service company with a deserve salary. Fifteen student and five teachers from vocational schools number IDepok Sleman Yogyakarta followed the program. The teaching method,which was used for the program, was speech and answering a question,demonstration and practice, and industrial survey. The practice programwas done trice by making six kinds of food and industrial survey in twoprospective food companies at Yogyakarta. The result of the civil serving program is very satisfying. It can beseen by the absence and the followers anthusiasm. The practice results arewell and maximum, the taste of the foods are good. Industrial Survey,which has never been done befote, is an interesting and exciting learningsituation. Keywords: entrepreneurship, live skills, and vocational school